Bilanzierung von Pensionsverpflichtungen : HGB, EStG und IFRS / IAS 19 /: HGB, EStG und IFRS / IAS 19. (2016) - Derbort, Stephan; Herrmann, Richard; Mehlinger, Christian; Seeger, Norbert
No abstract available